The Effect of GEMAS on Mathematical Problem-Solving and Critical-Thinking Abilities - Lukman, Hamidah Suryani; Setiani, Ana (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This research focuses on the development of gamification-based mathematics teaching materials specifically designed to improve the problem-solving and critical mathematical thinking skills of junior high school students in the form of GEMAS (Junior High School Mathematics Game) and to test the product based on its validity, practicality, and effectiveness aspects. The ADDIE MODEL is used in the research and development of GEMAS. Previous research articles have discussed the stages of product development, validity testing, and practicality, so the focus mof this article only discusses its effectiveness test. Thus, the stages of the ADDIE model used in this article are also limited to the last two stages, namely Implementation and Evaluation. The study was conducted at two junior high schools in Sukabumi using a one-sample pretest-posttest design. The sample was 256 students from 10 study groups using cluster random sampling techniques. Data were collected through the Krulik-Rudnick problem-solving ability test instrument, the FRISCO critical-thinking ability test, and student response sheets that met the criteria of being very valid and highly reliable. Data were analyzed using a paired two-sample t-test at a significance level of alpha 5% and descriptive analysis. The results of the study showed that GEMAS met the criteria for effectiveness. This can be seen from the overall range of values between the average pretest and posttest of problem-solving ability which reached 43.75 and critical thinking ability which reached 47.00, as well as the n-gain value of both mathematical problem-solving ability and mathematical critical thinking ability of junior high school students has met the moderate improvement category (46-51%).